Impact Of Domestic Violence on Mental and Physical Health of Women: A Case Study - Md. Alomgir Hossan; Priya Rani; Shopnil Chandra Sarker (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study investigates the impact of domestic violence on the mental and physical health of women in the 9th No. Kirtipur Union, Naogaon Sadar, based on a case study involving structured interviews with 100 women who have experienced domestic abuse. The research employs a quantitative approach to analyze the prevalence and consequences of such violence. The findings reveal widespread psychological trauma such as anxiety, depression, and post-traumatic stress disorder (PTSD), alongside physical ailments like chronic pain, fatigue, and reproductive health complications. The study further highlights the exacerbating role of socio-economic conditions, including poverty, gender inequality, cultural stigma, and limited access to healthcare, in deepening the victims’ suffering. Through a human-centered lens, this paper scrutinizes the urgent need for policy reform, community-based interventions, and comprehensive support systems to assist survivors. Ultimately, the research contributes to the global discourse on gender-based violence and offers practical recommendations for improving the well-being of affected women in both rural Bangladesh and similar socio-cultural conditions.